Biopolitics in Strindberg’s The Father - Mariam , Olya Mariam (Journal of Research in Humanities, 2023)
: The Father, written by Strindberg is a play about the Captain and Laura (husband and wife), both of whom are engaged in political maneuvering. Through these two, Strindberg has portrayed politics at a domestic level. If Foucalt’s concept of biopower is kept in mind, namely what measures a government takes for its survival and the reasons given for its existence, we can see how biopolitics work with reference to the power struggle between Laura and her husband. Strindberg delineates how the governance of the house incorporates alliances, coercion, wordplay, even the child, Bertha, is used as a pawn in this battle for domination. Both the Captain and Laura use the authoritarian style of governance; the Captain reigns as a monarch whereas Laura is more of a benevolent dictator. Since Laura is more adept at manipulation she is the one who reigns supreme at the end of the play.